2019
DOI: 10.1002/bab.1783
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of cadmium by potential probiotic Pediococcus pentosaceus using in vitro digestion model

Abstract: An exponential increase of heavy metal toxicant in the human body is a growing health-related problem. In the present study, Pediococcus pentosaceus FB145 and FB181 strains were isolated from fermented seafood and served as highly Cd-resistant strains. The unchanged structural cells of P. pentosaceus strains after treatment with Cd cations were investigated using a scanning electron microscope energy dispersive X-ray analysis. Furthermore, both P. pentosaceus strains showed strong human gastrointestinal tract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…P. pentosaceus not only affected the substance absorption and excretion of the intestine but also upregulated toxic substance decomposition by the detoxification ability of the liver, such as reducing blood ammonia, heavy metal ion, and endotoxin levels [49]. Le and Yang [50] carried out experiments to show that P. pentosaceus FB145 and FB181, derived from fermented seafood, were capable of reducing the toxicity of cadmium (Cd). They found that Cd combined with bacterial cells by specific several functional groups and thus decreased Cd bioaccessibility in vitro to 44.7-46.8%.…”
Section: Lipid-lowering Effectsmentioning
confidence: 99%
“…P. pentosaceus not only affected the substance absorption and excretion of the intestine but also upregulated toxic substance decomposition by the detoxification ability of the liver, such as reducing blood ammonia, heavy metal ion, and endotoxin levels [49]. Le and Yang [50] carried out experiments to show that P. pentosaceus FB145 and FB181, derived from fermented seafood, were capable of reducing the toxicity of cadmium (Cd). They found that Cd combined with bacterial cells by specific several functional groups and thus decreased Cd bioaccessibility in vitro to 44.7-46.8%.…”
Section: Lipid-lowering Effectsmentioning
confidence: 99%
“…The Pediococcus pentosaceus FB145 and FB181 strains, which can be considered as probiotic microorganisms, were suggested as potent biosorbents for preventing cadmium toxicity and reducing its absorption into the human body [97]-one more utility of biosorption, in this case, directly related to human health.…”
Section: Cadmium (Ii)mentioning
confidence: 99%
“…Due to these attributes, strain TA4 possessed an advantage in its biotechnological application in the bioremediation, food, and pharmaceutical industry. Moreover, its ability to bind Zn 2+ would be useful in preventing excessive dietary Zn 2+ toxicity in animals and human gut [67] and in the removal of high concentration of Zn 2+ from consumption of water and liquid food [20]. Notably, zinc-enriched LAB was reported to possess beneficial effects on living organisms [50].…”
Section: O-h Stretching and N-h Asymmetric Stretchingmentioning
confidence: 99%